Comparative Governance of Coffee Plantation Sector in Gayo Lues and Bener Meriah Regencies: A Public Administration Perspective - Rafika Duri; Harapan Tua; Firman Firman; Barlian Erliadi (Jurnal Ilmu Administrasi Negara (JUAN), 2026)
The coffee plantation sector plays a strategic role in supporting rural economic development, farmer welfare, and regional competitiveness in the highlands of Aceh. Gayo Lues Regency and Bener Meriah Regency are two important areas in the development of Gayo Arabica coffee, yet both regions demonstrate different governance characteristics in terms of institutional capacity, farmer organization, market access, cultivation innovation, and local government policy effectiveness. This study aims to compare the governance of the coffee plantation sector in Gayo Lues and Bener Meriah from the perspective of public administration. The research employs a descriptive qualitative approach using a comparative case study strategy based on literature review and secondary data analysis. The analytical framework draws on the concepts of governance, collaborative governance, good governance, and comparative public administration to identify the factors that shape governance performance in both regions. The findings show that Bener Meriah has relatively stronger governance performance due to the active role of farmer cooperatives, better integration with export markets, stronger collaboration between local government and non-state actors, and more adaptive support for farmer empowerment. In contrast, Gayo Lues has considerable land potential but continues to face challenges related to infrastructure, distribution access, weak farmer economic institutions, and limited market connectivity. These conditions indicate that differences in institutional capacity, policy orientation, value chain structure, and human resource development significantly influence the effectiveness of coffee plantation governance. The study recommends strengthening collaborative governance in Gayo Lues through cooperative development, participatory policymaking, infrastructure improvement, farmer capacity building, and cross-sectoral policy integration to enhance the competitiveness and welfare of coffee farmers in both regions.